Solidarity in action: Swiss library projects for Ukraine’s future - Bezpala Halyna; Kurmann Anastasiia (Наукові праці Національної бібліотеки України імені В.І. Вернадського)

(untitled)
Purpose of the article to explore Swiss support projects for Ukraine amidst the backdrop of war, involving local institutions and individuals. It specifically delvesin to the aid provided to the school library in Putylovychi, while also scrutinizing the educational, cultural events, and social integration programs conducted by the City Library of Winterthur for Ukrainian refugees. Methodology. Employing systemic and structural methodologies, including an interdisciplinary approach, the research seeks to shed light on novel insights. Scientific novelty. The study introduces a fresh perspective on understanding the significance of educational and cultural endeavors within conflict zones. Moreover, it identifies practical strategies to enhance local infrastructure amidst ongoing hostilities. Notably, it highlights the pivotal role of libraries as a point of contact for Ukrainian refugees abroad, examining the impact of diverse integration programs and cultural initiatives on refugee adaptation andsupport. Conclusions. Switzerland’s support for Ukraine’s journey towards peaceand sustainable development underscores the principle of equal citizen participation in societal well-being and national progress. The findings underscore the effectiveness of library initiatives in conflict areas and countries hosting Ukrainian refugees, showcasing their contribution to successful adaptation and improved quality of life. Such initiatives exemplify Switzerland’s collaborative responsibility with European nations for Ukraine’s future and its solidarity against Russian aggression.